2019
DOI: 10.1177/0040517519848161
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of raising on the sound absorption behavior of polyester woven fabrics

Abstract: This work presents the results of efforts focused on the development of sound absorptive woven fabrics by the raising process. Four woven fabrics with rib and basket weave patterns were produced for the raising process. Micro-fiber-based polyester weft yarns were used in one set of rib and basket weave fabrics, while weft yarns comprising regular polyester fibers were used in the other set. Fabrics were subjected to dyeing and heat setting prior to the raising process. Fabrics were then passed one to three tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…It was found that the plain fabric had a higher sound absorption than the other weave types. [19][20][21] In this experiment, three kinds of woven fabrics with plain weave, twill weave and satin weave were prepared (Figures 6 (a)-(c)). It can be found that the shape and size of the pore structure in woven fabrics with different fabric textures were obviously varied.…”
Section: Sound Absorption Of Woven Fabricsmentioning
confidence: 99%
“…It was found that the plain fabric had a higher sound absorption than the other weave types. [19][20][21] In this experiment, three kinds of woven fabrics with plain weave, twill weave and satin weave were prepared (Figures 6 (a)-(c)). It can be found that the shape and size of the pore structure in woven fabrics with different fabric textures were obviously varied.…”
Section: Sound Absorption Of Woven Fabricsmentioning
confidence: 99%
“…Ses, gözenekli yapıya girdiği zaman, frekansa bağlı olarak, küçük hava hacimlerini gözenekli yapının boşluklarında salınım yaptırır. Bu küçük hava hacimlerinin bir bölümü liflerle temas halinde olduğundan sürtünme kayıpları olur, buda enerji kaybına yol açar (Suvari ve Dulek, 2019).…”
Section: Introductionunclassified
“…16,17 Although it is difficult to produce textured surfaces with nonwoven fabrics for an aesthetically pleasing appearance, nonwoven fiber webs are usually draped with woven fabrics for enhanced structural stability. 18 As well, plain weft-knitted fabric is also proposed for applications in sound absorption, while its sound-absorption performance is relatively poor. 19 Considering this case, numerous attempts have been made to improve the sound-absorption ability of knitted fabrics currently.…”
mentioning
confidence: 99%